2021
DOI: 10.1021/acsaem.1c01385
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly of Nanostructured Conducting Polymer Hydrogels by Hydrotropic Agents for Outstanding Supercapacitive Energy Storage

Abstract: Conducting polymer hydrogels (CPHs) are relevant to energy storage due to their micro-nanoscale three-dimensional network combined with a high electronic conductivity and electrochemical activity. The successful implementation of CPHs as an energy storage material requires solving two barriers: (1) low capacitance and electronic conductivity of current CPHs and (2) the lack of simple and scalable chemical synthesis routes. In this work, we propose a different approach for the synthesis of CPHs based on a supra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…For over 150 years, the diverse chemistry, and fascinating electroactive properties of conducting polymers have been known to the scientific community. 14 Conducting polymers owing to the extensive main-chain p-conjugation radically increase the rigid rod chain stiffness of the polymer backbone, which can be chemically manipulated by the nature and degree of doping and via blending with conventional polymers thus tuning the molecular structure for use in biochemical sensors, [15][16][17] corrosion protection of metals, 18,19 electromagnetic interference shielding, 20 electrostatic discharge protection 21 and a variety of explicit applications. 22 Lately, the application of conductive polymer (CP)-based anticorrosive coatings has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For over 150 years, the diverse chemistry, and fascinating electroactive properties of conducting polymers have been known to the scientific community. 14 Conducting polymers owing to the extensive main-chain p-conjugation radically increase the rigid rod chain stiffness of the polymer backbone, which can be chemically manipulated by the nature and degree of doping and via blending with conventional polymers thus tuning the molecular structure for use in biochemical sensors, [15][16][17] corrosion protection of metals, 18,19 electromagnetic interference shielding, 20 electrostatic discharge protection 21 and a variety of explicit applications. 22 Lately, the application of conductive polymer (CP)-based anticorrosive coatings has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids are preferred due to their good compatibility with resins. In this study, the chelation ability of organic acids [camphor sulphonic acid (CSA), 18 p -toluene sulphonic acid ( p -TSA), 18 and sulfosalicylic acid (SSA)] 39,40 with an aluminum alloy was assessed. The anti-corrosion behavior of doped CPs in an epoxy matrix was also evaluated via EIS.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the robustness and the mechanical performance of the conducting polymer-based hydrogel for epidermal bioelectronics, the supramolecular crosslinking strategies between rigid conducting polymers and soft polymers have been investigated. [13][14][15][16][17] Li et al reported a high performance, flexible, solid-state supercapacitor based on the supramolecular assembly of polyaniline (PANI) and polyvinyl alcohol (PVA), made through boronate bonds. 14 The developed supercapacitor exhibited a specific capacitance of 153 F g À1 , with a high energy density of 13.6 W h kg À1 .…”
Section: Introductionmentioning
confidence: 99%
“…4−6 In particular, in situ UV−vis−NIR spectroelectrochemistry has been widely employed to evaluate the electronic transitions involved in the charging/discharging process of π-conjugated polymers. 7−12 These materials have received increasing attention due to their possible use in sensing, 13−15 energy storage and conversion, 16 and environmental remediation, 17 as well as in bioelectronics, 18,19 and neuromorphic computing. 20 Nevertheless, the type of charge carrier, e.g., σ-dimers, πdimers, polaron pair, and bipolaron, and the mechanisms of charge carrier transport, intrawire and interwire, remains still a point of discussion.…”
mentioning
confidence: 99%
“…Among the different spectroscopies coupled with electrochemistry, UV–vis is one of the most used techniques due to the simple correlation between the absorption changes and the simultaneous electrochemical measurements. This technique has been used to study not only single step electron-transfers, but also multistep redox reactions or the formation of mixed-valence intermediates. In particular, in situ UV–vis–NIR spectroelectrochemistry has been widely employed to evaluate the electronic transitions involved in the charging/discharging process of π-conjugated polymers. These materials have received increasing attention due to their possible use in sensing, energy storage and conversion, and environmental remediation, as well as in bioelectronics, , and neuromorphic computing . Nevertheless, the type of charge carrier, e.g ., σ-dimers, π-dimers, polaron pair, and bipolaron, and the mechanisms of charge carrier transport, intrawire and interwire , remains still a point of discussion. , Thus, an important aspect in conducting polymer (CP) research is to develop in situ spectroelectrochemical methods that allow real-time monitoring of the electrochemical, electric, and optical properties of conducting materials.…”
mentioning
confidence: 99%